Seismic Assessment of Non-conforming Infilled RC Buildings Using IDA Procedures - Repapis, Constantinos; Zeris, Christos A. (Frontiers in Built Environment, 2019)
The seismic performance of existing non-conforming reinforced concrete (RC) buildings is numerically investigated, taking into account the presence of clay brick masonry infill walls. The effect of infill walls on the seismic response of RC frames is widely recognised and has been a subject of numerous analytical and experimental investigations. In this context, Static Pushover analyses of typical existing RC infilled frames have established these structures’ inelastic characteristics, focusing on the significant contribution of infill walls to their dynamic characteristics, overstrength, form irregularity and damage. Furthermore, more comprehensive studies of inelastic static response considered the typical variability among different generations of constructed buildings in Greece since the 60s in the form, the seismic design and detailing practice and the structural materials, with different masonry infill configurations and properties. In the present study, the results from such Static Pushover analyses are extended with Incremental Dynamic Analysis predictions using a large number of recorded base excitation from recent destructive earthquakes in Greece and abroad. Evaluation of the time history predictions and comparisons with the Static Pushover analysis findings corroborate that the presence of regular arrangements of perimeter infill walls increase considerably the stiffness and resistance to lateral loads of the infilled RC structures, while at the same time, reducing their global ductility and deformability. Fully or partially infilled RC frames can perform well, while structures with an open floor usually exhibit the worse performance by creating an unintentional soft storey. The analyses further prove that lower strength masonry provides the building with lower overstrength but higher ductility.